Incidencia de microorganismos eficientes más abonos orgánicos en el comportamiento agronómico del cultivo de cebolla (Allium cepa) en el Cantón La Maná - Llanos Calero, Cristhian Homero (2013)
The present study was conducted in the La Maná Canton, province of Cotopaxi, sector The Playita, is located between the coordinates geographical 00 ° 49' 00 "South latitude and 78 ° 48'30" West longitude. The experimental work lasted for three months. The treatments under study were as follows: T1 = organic fertilizer Agropesa (50L ha-1) Azotobacter spp. (1 L ha-1) T2 = manure organic Agropesa (50L ha-1) Pseudomonas fluorescens (1L ha-1) T3 = manure organic Biol (50L ha-1) Azotobacter spp. (1 L ha-1)T4 = manure organic Biol (50L ha-1) Pseudomonas fluorescens (1L ha-1) Was the design of completely randomized blocks DBCA with a total of four treatments and five replicates, with which was obtained 20 units experimental The results were: the largest average in treatments at 30 days the organic fertilizer Agropesa Azotobacter spp. The results were: height of organic fertilizer treatment plant Biol + Azotobacter spp, reached the altitude with 26.25 cm to 30 days; 45, 60 and 90 days the organic fertilizer Biol + Pseudomonas fluorescens reach their maximum height with 36.90, 54.04 and 70.47 cm in its corresponding order treatment, organic fertilizer Agropesa + Azotobacter spp. manure organic Agropesa and + Pseudomonas fluorescens have a similarity in fruits with 1.50; getting The value higher in organic fertilizer plant diameter Agropesa + Azotobacter spp, with 4.25 cm; the weight was detected with higher yielding organic fertilizer Agropesa + Pseudomonas fluorescens with 140.34 g and profitability per hectare with 1.41 t. In terms of economic analysis, optimal net income was given treatment 4 fertilizer organic biol Pseudomonas fluorescens, 16.49 USD, this same treatment obtained in the relation benefit/cost with the 0.32.